Effects of salt stress on growth and metabolism of tomato (Solanum lycopersicum L.) plants associated with high concentration of carbon dioxide - Brito, Fred Augusto Lourêdo de (2020)
Soil salinity is an important environmental factor that limits the crop yield. On the other hand, the elevated CO2 concentration (e[CO2]) is able to mitigate the negative effects of salt stress on crop yield by stimulating photosynthetic rate in many C3 species, including Solanum lycopersicum. However, the impact of soil salinization on the relationship between biomass allocation, hormone biosynthesis and the primary metabolism of tomato plants under e[CO2] are hitherto not well understood. In this context, tomato plants grown under salt stress showed high Na+ concentration in tissues under both ambient [CO2] (a[CO2]) and e[CO2]. Under a[CO2], plants treated with NaCl showed lower accumulation of biomass compared to untreated plants. However, e[CO2] restored the growth of tomato plants under saline stress by reducing concentration of abscisic acid (ABA) and the ethylene precursor 1-aminocyclopropane-1- carboxylic acid in leaves and roots. In addition, plants treated with NaCl under a[CO2] showed reduction of the concentration of Krebs Cycle intermediates and increase of amino acids glycine and serine, while the plants under e[CO2] treated with NaCl presented the recovery of these parameters to the levels of the control plants. These findings led to a new questioning whether plants with alterations in ABA biosynthesis present differential strategies of tolerance to saline stress under e[CO2]. Thus, we analyzed tomato plants cv. Micro-Tom (MT), ABA-deficient mutant notabilis (not) and plants with high ABA concentration (NCED) submitted to salt stress. The growth of not plants was more affected in relation to MT and NCED plants, mainly under conditions of salt stress under both [CO2]. On the other hand, e[CO2] led to increases in total biomass and leaf area for all genotypes under saline stress, compared to a[CO2]. In addition, NCED mutants showed greater growth in relation to the MT and not genotypes under e[CO2] in control and saline conditions. e[CO2] caused an increase in photosynthesis and reduction of photorespiration in the MT, not and NCED treated with NaCl compared to a[CO2]. In addition, e[CO2] induced changes in the primary metabolism which were associated with increases in dark respiration, especially of MT and not genotypes under saline stress. Taken together, our results suggest that e[CO2] alleviates the effects of saline stress on plants through increased photosynthesis, reduced photorespiration and reprogrammed primary metabolism by mechanisms independent of ABA concentration. Keywords: Photosynthesis. Respiration. Primary metabolism. Hormonal regulation. Salt stress. Tomato plant